2014
DOI: 10.1245/s10434-014-3943-8
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Sentinel Lymph Node Biopsy in Patients with Ductal Carcinoma In Situ Suspicious for Microinvasion on Core Biopsy

Abstract: In patients with Smic on CNB, the incidence of macrometastatic nodal disease after SLNB is rare. Surgeons may consider omitting SLNB until IDC is definitively confirmed, especially in patients with Smic apart from other high-risk features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…4,10,12,13 Reported rates for performance of SLNB for DCIS range from 21 to 97 %, but these rates are reported primarily from single-institution studies examining predictors of SLNB positivity, which select for tumors with high-risk characteristics. 6,[14][15][16] In 2010, the rate was 17.8 % for lumpectomy patients and 67.1 % for mastectomy patients in the Surveillance, Epidemiology, and End Results (SEER) database, although this was based on the number of lymph nodes examined rather than the specific type of axillary surgery. 17 In 2012, the National Cancer Data Base (NCDB) began collecting information on whether SLNB or axillary lymph node dissection (ALND) was performed in addition to the number of nodes removed.…”
mentioning
confidence: 99%
“…4,10,12,13 Reported rates for performance of SLNB for DCIS range from 21 to 97 %, but these rates are reported primarily from single-institution studies examining predictors of SLNB positivity, which select for tumors with high-risk characteristics. 6,[14][15][16] In 2010, the rate was 17.8 % for lumpectomy patients and 67.1 % for mastectomy patients in the Surveillance, Epidemiology, and End Results (SEER) database, although this was based on the number of lymph nodes examined rather than the specific type of axillary surgery. 17 In 2012, the National Cancer Data Base (NCDB) began collecting information on whether SLNB or axillary lymph node dissection (ALND) was performed in addition to the number of nodes removed.…”
mentioning
confidence: 99%
“…Besides, when small cancer nests or single cells seem to be focally extending out from DCIS, it is challenging to tell whether these cells are truly invasive or not. 9 These cases are diagnosed as DCIS with suspicious microinvasion. In this study, we found that DCIS with suspicious microinvasion was the single most significant pathological feature that correlated with upgrading risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are concordant with the only other study that, to our knowledge, addresses this topic. 5…”
Section: Presentmentioning
confidence: 99%